2012
DOI: 10.1371/journal.pone.0045687
|View full text |Cite|
|
Sign up to set email alerts
|

Effet of Combined Nitrogen Dioxide and Carbon Nanoparticle Exposure on Lung Function During Ovalbumin Sensitization in Brown Norway Rat

Abstract: The interaction of particulate and gaseous pollutants in their effects on the severity of allergic inflammation and airway responsiveness are not well understood. We assessed the effect of exposure to NO2 in the presence or absence of repetitive treatment with carbon nanoparticle (CNP) during allergen sensitization and challenges in Borwn-Norway (BN) rat, in order to assess their interactions on lung function and airway responses (AR) to allergen and methacholine (MCH), end-expiratory lung volume (EELV), bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…However, despite these cellular changes, there was no evidence of altered lung responsiveness to MCh. Following sensitization with aerosolized OVA, the coexistence of bronchial inflammation and the lack of BHR to non‐specific constrictor challenge are controversial, but our findings are in accordance with results indicating dissociated inflammatory and mechanical responses …”
Section: Discussionsupporting
confidence: 90%
“…However, despite these cellular changes, there was no evidence of altered lung responsiveness to MCh. Following sensitization with aerosolized OVA, the coexistence of bronchial inflammation and the lack of BHR to non‐specific constrictor challenge are controversial, but our findings are in accordance with results indicating dissociated inflammatory and mechanical responses …”
Section: Discussionsupporting
confidence: 90%
“…As a positive control for IgE-mediated allergic inflammation, the OVA-induced allergic airway inflammation model was established according to the previously described method, with slight modification [ 35 ]. Briefly, 6-week old female Wistar rats were sensitized on days 0, 7, and 14 with an intraperitoneal injection of 1 mg OVA (Grade V, Sigma-Aldrich, St Louis, MO, USA) and 100 mg aluminum hydroxide (Sigma-Aldrich) in 1 mL sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…Recent in vitro findings suggested that levels of SO 2 and NO 2 below current EU health based exposure standards can exacerbate pollen allergy on susceptible subjects (Sousa et al, 2012). Moreover, exposure to NO 2 significantly enhanced lung inflammation and airway reactivity in animals that were treated with ovalbumin (Layachi et al, 2012). So, there are mixed results in human clinical studies in which NO 2 exposure preceded allergen exposure.…”
Section: Pmmentioning
confidence: 99%